2021
DOI: 10.2196/17185
|View full text |Cite
|
Sign up to set email alerts
|

Internet and Face-to-face Cognitive Behavioral Therapy for Postnatal Depression Compared With Treatment as Usual: Randomized Controlled Trial of MumMoodBooster

Abstract: Background Previous research has confirmed that symptoms of postnatal depression (PND) can be ameliorated through internet-delivered psychological interventions. Advantages of internet-delivered treatment include anonymity, convenience, and catering to women who are unable to access face-to-face (FTF) treatments. To date, no research has examined the efficacy of such interventions compared directly with FTF treatments in women clinically diagnosed with PND. Objecti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 107 publications
1
32
1
Order By: Relevance
“…In conclusion, in a feasibility trial of depressed pregnant women, the Mum2BMoodBooster program was found to be promising as an online CBT therapy for the alleviation of low mood in pregnancy, including those with a major depressive disorder. Outcomes were similar to those reported with the postnatal version of the program in RCTs, including good acceptability and adherence [ 16 , 25 , 26 ]. Like the postnatal version, this therapy was delivered in conjunction with weekly (approximately 30 min) supportive telephone calls from a coach.…”
Section: Discussionsupporting
confidence: 66%
See 4 more Smart Citations
“…In conclusion, in a feasibility trial of depressed pregnant women, the Mum2BMoodBooster program was found to be promising as an online CBT therapy for the alleviation of low mood in pregnancy, including those with a major depressive disorder. Outcomes were similar to those reported with the postnatal version of the program in RCTs, including good acceptability and adherence [ 16 , 25 , 26 ]. Like the postnatal version, this therapy was delivered in conjunction with weekly (approximately 30 min) supportive telephone calls from a coach.…”
Section: Discussionsupporting
confidence: 66%
“…This was despite the relatively low level of baseline anxiety in the study sample, which averaged in the “normal” range (stress scores were in the “mild” range). Although RCTs of the postnatal program [ 16 , 26 ] showed larger reductions in anxiety and stress than seen here, baseline levels of anxiety and stress were higher. Whilst anxiety levels in this study sample appeared mild, anxiety often accompanies perinatal depression, affecting 7.9% of antenatal women [ 35 ].…”
Section: Discussioncontrasting
confidence: 50%
See 3 more Smart Citations